Evaluating the performance of Calcium Carbide Kiln Dust in mortar - Initial study - Latif M.A.; Naganathan S.; Razak H.A.; Mustapha K.N. (Elsevier Ltd, 2023)
Byproducts; Calcium; Calcium carbide; Cements; Compressive strength; Density (specific gravity); Dust; Kilns; Mixtures; Mortar; Physical properties; Portland cement; Setting; Cement based material; Cement replacement; Durability of concretes; Environmental pollutions; Kiln dust; Mortar strength; Ordinary Portland cement; Research and development; Strength of materials